A Dual-Perspective Case Study - Analysing the Strategic-Operational Disconnect in Digital Procurement Adoption within a Multinational FMCG Organisation - Sasikumar, Gautam (Cranfield University, 2025)
Digital Transformation in the Fast-Moving Consumer Goods (FMCG) sector is often undermined by non-technical challenges, creating a persistent “strategic-operational” disconnect where investments in procurement technology fail to achieve intended value due to misalignment between the leadership’s strategic intent and user adoption. Current literature usually treats these macro (organisational) and micro (user) adoption challenges in isolation, failing to capture the complexities existing in the socio-technical reality. This study employs an in-depth, single-case study design within a multinational FMCG corporation headquartered in London, utilising a dual-perspective qualitative methodology, involving semi-structured interviews with organisational leaders and end users. The data was collected using a comprehensive theoretical framework that covers individual-level theories such as Technology Acceptance Model and Unified Theory of Acceptance and Use of Technology, and organisational-level theories such as Diffusion of Innovations, Resource-Based View and Socio-Technical Systems. The findings confirmed a fundamental disconnect: while leaders prioritised strategic drivers such as automation and compliance in procurement, user adoption was actively hindered by micro-level issues covering poor usability and conditional utility. This “resistance” was found to be a rational response to a cumbersome tool than mere behavioural inertia, challenging the leadership’s perception of an entrenched “culture of convenience” amongst users. Data triangulation confirms that this disconnect demonstrates a breakdown of the socio-technical system. The study concludes that overall strategic value from a new procurement technology is unattainable unless technology design and implementation in procurement are strongly driven by the tangible, effortless utility for the end-user. This work contributes a holistic, empirically grounded analysis, extending existing adoption theories by providing a multi-level view essential for effective change management to improve adoption.
Keywords: Technology Adoption; Digital Transformation; Digital Procurement; Leadership Perspective; User Perspective; Change Management; User Resistance; Automation; Compliance; Technology Acceptance Model; Unified Theory of Acceptance and Use of Technology; Diffusion of Innovation; Technology-Organisation-Environment framework; Resource-Based View; Dynamic Capability; Institutional Theory; Sociotechnical Systems Theory and Digital Divide Theory